Design, Synthesis, Antiviral Evaluation, and SAR Studies of New 1-(Phenylsulfonyl)-1H-Pyrazol−4-yl-Methylaniline Derivatives - Desideri, Nicoletta; Fioravanti, Rossella; Proietti Monaco, Luca; Atzori, Elena Maria; Carta, Antonio; Delogu, Ilenia; Collu, Gabriella; Loddo, Roberta (Frontiers in Chemistry, 2019)
A series of N-((3-phenyl-1-(phenylsulfonyl)-1H-pyrazol-4-yl)methyl)anilines 6a-b’, structurally related to previously synthesized and tested (N-(1,3-diphenyl-1H-pyrazol-4-yl)methyl)anilines (1a-v), were designed and synthesized. The new derivatives were evaluated in cell-based assays for their cytotoxicity and antiviral activity against a large panel of RNA and DNA viruses of public health significance. Generally, the tested compounds did not display cytotoxicity towards the cell lines used. The majority of derivatives 6a-p were able to interfered with YFV and RSV replication in the micromolar range showing a marked improvement in potency and selectivity with respect to the reference inhibitors 6-azauridine and ribavirin, respectively. The introduction of a p-methoxy substituent on the phenylsulfonyl group (compounds 6q-b’) completely abolished the anti-RSV activity and reduced or eliminated the potency against YFV. On the contrary, several p-methoxy analogues were able to interfere with BVDV replication with a comparable o better potency than the reference inhibitor, ribavirin. Compound 6e, selected for time of addition experiments on BHK-21 cell cultures infected with YFV, achieved the highest reduction of virus titre when added 2 hrs post infection and maintained up to 4 hrs post infection.